2016
DOI: 10.2298/hemind140830013j
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of Ruscus species from Serbia: Potential new sources of natural antioxidants

Abstract: The antioxidant activity and total phenolic and flavonoid content of ethanolic, acetone and ethyl acetate extracts of Ruscus hypoglossum L. and Ruscus aculeatus L. (aerial parts) from Serbia were investigated in this paper. The best total antioxidant capacity (23.329 μg AA g-1) and the highest DPPH scavenging activity (IC 50 = 182.54 μg mL-1) were found in acetone and ethyl acetate extract of R. aculeatus L. Ethanolic extract of R. hypoglossum L. showed the highest ABTS radical cation scavenging activity (IC 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…In another study, ethanol, acetone and ethyl acetate extracts obtained using Soxhlet method from the aerial parts of the plant and antioxidant activities of these extracts were investigated. In this study, acetone and ethyl acetate extracts showed the best total antioxidant capacity (23.329 μg AA g -1 ) and the highest DPPH scavenging activity (IC 50 = 182.54 μg mL -1 ) respectively 16 .…”
Section: Anticholinesterase Activitymentioning
confidence: 54%
See 1 more Smart Citation
“…In another study, ethanol, acetone and ethyl acetate extracts obtained using Soxhlet method from the aerial parts of the plant and antioxidant activities of these extracts were investigated. In this study, acetone and ethyl acetate extracts showed the best total antioxidant capacity (23.329 μg AA g -1 ) and the highest DPPH scavenging activity (IC 50 = 182.54 μg mL -1 ) respectively 16 .…”
Section: Anticholinesterase Activitymentioning
confidence: 54%
“…This plant is used for treatment of venous insufficiency / varicosities edema such as circulatory disorders, edema, thrombophlebits, swelling and also used as diuretic. Also it is used in premenstrual syndrome, hemorrhoids, diabetic retinopathy, skin disease, against inflammation and arthritis [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Luís et al [ 16 ] described that the methanolic extract of the aerial part showed little antioxidant activity in the DPPH assay, with an IC 50 value of 171.9 mg/L. Other studies, using also the aerial part, reported that ethyl acetate and butanol extracts were the ones that revealed the best activity for the DPPH assay, and obtained EC 50 values of 158 and 173 μg/mL, respectively [ 20 ] and, Jakovljević et al [ 12 ] obtained EC 50 values of 183 μg/mL of ethyl acetate extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Few research groups have already studied this species [ 11 , 12 , 13 ]; the same authors report that the main active ingredients found in R. aculeatus are steroidal saponins (rucogenin and neoruscogenin), which are responsible for its pharmacological effects; other constituents have been isolated, including sterols, triterpenes, flavonoids, coumarins, sparteine, tyramine, and glycolic acid. Moreover, some of the traditional applications of the species seem related to particular compounds, since the highest concentration of ruscogenins is located in the rhizome [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ABTS•+ radical cation decolorization assay was performed spectrophotometric method. The ABTS+ scavenging activity was calculated previously described by Jakovljević (Jakovljević VD et al, 2016). Briefly, ABTS stock solution (7 mM) with 2.45 mM potassium persulfate.…”
Section: Abts Decolorization Assaymentioning
confidence: 99%